Administration of breast milk cell fractions to neonates with birthweight equal to or less than 1800 g: a randomized controlled trial - Minoo Fallahi; Seyed Masoud Shafiei; Naeeme Taslimi Taleghani; Maryam Khoshnood Shariati; Shamsollah Noripour; Fatemeh Pajouhandeh; Sina Kazemian; Mahmood Hajipour; Mohammad Kazemian (BMC, 2021)
Abstract Background Most premature and very low birthweight infants cannot tolerate breast milk feeding in the first few days of life and are deprived of its benefits. This study evaluates the clinical outcomes of administering breast milk cell fractions to neonates with a birthweight of ≤1800 g. Methods We conducted a randomized controlled trial on 156 infants in the neonatal intensive care unit of Mahdieh Maternity Hospital in Tehran, Iran, from May 2019 to April 2020. All neonates with a birthweight ≤1800 g were enrolled and divided into intervention and control groups using stratified block randomization. Neonates in the intervention group received the extracted breast milk cell fractions (BMCFs) of their own mother's milk after being centrifuged in the first 6 to 12 h after birth. The control group received routine care, and breastfeeding was started as soon as tolerated in both groups. Study outcomes were necrotizing enterocolitis (NEC), death, and in-hospital complications. Results We divided participants into two groups: 75 neonates in the intervention group and 81 neonates in the control group. The mean birthweight of neonates was 1390.1 ± 314.4 g, and 19 (12.2%) neonates deceased during their in-hospital stay. The incidence of NEC was similar in both groups. After adjustment for possible confounders in the multivariable model, receiving BMCFs were independently associated with lower in-hospital mortality (5 [26.3%] vs. 70 (51.1%]; odds ratio (OR): 0.24; 95% confidence interval [CI] 0.07, 0.86). Also, in a subgroup analysis of neonates with birthweight less than 1500 g, in-hospital mortality was significantly lower in the intervention group (4 [9.5%] vs. 13 [30.2%]; OR: 0.24; 95% CI 0.07, 0.82). There were no differences in major complications such as bronchopulmonary dysplasia and retinopathy of prematurity between the two groups. No adverse effects occurred. Conclusions Our research demonstrated a significantly lower mortality rate in neonates (with a birthweight of ≤1800 g) who received breast milk cell fractions on the first day of life. Since this is a novel method with minimal intervention, we are looking forward to developing and evaluating this method in larger studies. Trial registration IIranian Registry of Clinical Trials. Registered 25 May 2019, IRCT20190228042868N1 .